2006
DOI: 10.1007/s11357-006-9017-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in neurocognitive aging of the medial temporal lobe

Abstract: A wide spectrum of outcomes in the cognitive effects of aging is routinely observed in studies of the elderly. Individual differences in neurocognitive aging are also a characteristic of other species, such as rodents and non-human primates. In particular, investigations at behavioral, brain systems, cellular and molecular levels of analysis have provided much information on the basis for individual differences in neurocognitive aging among healthy outbred rats. These findings are likely to be relevant to an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 73 publications
1
49
0
Order By: Relevance
“…Convergent data across animal and human studies have suggested that a key neural substrate for this decline is a shift in hippocampal network dynamics away from pattern separation and toward pattern com- pletion 72 , which appears to be mediated by CA3 hyperactivity 35,7376 and representational rigidity 35,72,75,77 —a failure to remap or manifest a novelty signal when stimuli are similar but not identical. These alterations may be closely linked to changes in the perforant path 7881 and to disinhibition in the DG and CA3 subregions resulting from the loss of inhibitory tone in GABAergic interneurons 72,82 .…”
Section: Age-related Cognitive Decline and Dementiamentioning
confidence: 99%
“…Convergent data across animal and human studies have suggested that a key neural substrate for this decline is a shift in hippocampal network dynamics away from pattern separation and toward pattern com- pletion 72 , which appears to be mediated by CA3 hyperactivity 35,7376 and representational rigidity 35,72,75,77 —a failure to remap or manifest a novelty signal when stimuli are similar but not identical. These alterations may be closely linked to changes in the perforant path 7881 and to disinhibition in the DG and CA3 subregions resulting from the loss of inhibitory tone in GABAergic interneurons 72,82 .…”
Section: Age-related Cognitive Decline and Dementiamentioning
confidence: 99%
“…4A, where the loss of the anticorrelated FC is represented as a net positive shift). A growing body of evidence suggests that successful cognitive outcomes in aging arise from active neurobiological adaption (42), perhaps comprising the substrates of cognitive resilience and reserve. Here, the affected network in AU rats involved frontoinsular circuitry implicated in switching between the DMN and executive control networks (41).…”
Section: Rsc/pcc Fc Is Widely Disrupted Selectively In Aged Rats Withmentioning
confidence: 99%
“…Exposure to an enriched environment during adulthood modifies many aspects of rodent behavior and improves learning and memory in a variety of tasks, especially those assessing spatial memory (e.g., Schrijver et al 2002;Leggio et al 2005;Birch et al 2013;Mora-Gallegos et al 2015). Evaluation of the effects of environmental enrichment on spatial memory is especially relevant in the context of physiological aging, as enrichment was shown to stimulate neuroplasticity in brain areas playing a major role in this cognitive domain (e.g., Faherty et al 2003;Leggio et al 2005;Birch et al 2013;, which is particularly sensitive to aging (Gallagher et al 2006). Several studies using cross-sectional experimental designs showed that spatial memory progressively declines during adulthood.…”
Section: Strasbourg Francementioning
confidence: 99%
“…For this longitudinal study, middle-aged (17 mo) rats were trained in a first reference memory task in a Morris water maze (i.e., finding an escape platform located in a fixed position in a pool), a place-learning task widely used to distinguish individuals with or without impaired learning and memory during aging (e.g., Gallagher et al 2006;Cassel et al 2007). Similar number of rats thereby classified as either unimpaired or impaired were subsequently housed for 6 mo in enriched environment (EE) or standard conditions (SC).…”
Section: Strasbourg Francementioning
confidence: 99%